Prevalence and factors associated with preterm birth at kenyatta national hospital - Peter Wagura; Aggrey Wasunna; Ahmed Laving; Dalton Wamalwa; Paul Ng'ang'a (BMC, 2018)
Abstract Background The World Health Organization estimates the prevalence of preterm birth to be 5-18% across 184 countries of the world. Statistics from countries with reliable data show that preterm birth is on the rise. About a third of neonatal deaths are directly attributed to prematurity and this has hindered the achievement of Millennium Development Goal-4 target. Locally, few studies have looked at the prevalence of preterm delivery and factors associated with it. This study determined the prevalence of preterm birth and the factors associated with preterm delivery at Kenyatta National Hospital in Nairobi, Kenya. Methods A cross-sectional descriptive study was conducted at the maternity unit of Kenyatta National Hospital in Nairobi, Kenya in December 2013. A total of 322 mothers who met the eligibility criteria and their babies were enrolled into the study. Mothers were interviewed using a standard pretested questionnaire and additional data extracted from medical records. The mothers' nutritional status was assessed using mid-upper arm circumference measured on the left. Gestational age was assessed clinically using the Finnstrom Score. Results The prevalence of preterm birth was found to be 18.3%. Maternal age, parity, previous preterm birth, multiple gestation, pregnancy induced hypertension, antepartum hemorrhage, prolonged prelabor rupture of membranes and urinary tract infections were significantly associated with preterm birth (p = < 0.05) although maternal age less < 20 years appeared to be protective. Only pregnancy induced hypertension, antepartum hemorrhage and prolonged prelabor rupture of membranes remained significant after controlling for confounders. Marital status, level of education, smoking, alcohol use, antenatal clinic attendance, Human Immunodeficiency Virus status, anemia, maternal middle upper arm circumference and interpregnancy interval were not associated with preterm birth. Conclusions The prevalence of preterm birth in Kenyatta National Hospital was 18.3%. Maternal age ≤ 20 years, parity > 4, twin gestation, maternal urinary tract infections, pregnancy induced hypertension, antepartum hemorrhage and prolonged prelabor rupture of membranes were significantly associated with preterm birth. The latter 3 were independent determinants of preterm birth. At-risk mothers should receive intensified antenatal care to mitigate preterm birth.